The Power of Folktale: Tackling the Marketing Gap by Preserving the Authentic Rendeng Village Pottery Designs - Adibah Nurul Yunisya; Heru Prasetiyo Utomo (Future Science)
Rendeng Village is a village located on the east of Java Island which famous for its pottery products. Its main products consist of tableware and piggy bank with various shapes and character. The piggy bank character produced by Rendeng Village is famous for its unique and authentic design which only produced form Rendeng Village. However, the selling demand and production for its established character beginning to decrease, which threatens its establishment as part of cultural products. This research aims to investigate folktale as a method to preserve a cultural fiction character by investigating the phenomena occurring in the establishment of Rendeng Village original character pottery products. The method used in this research is by analysing the cause of the decreasing demands of Rendeng Village original character pottery products, spatially, and non-spatially. Furthermore, this research explores the elements required in preserving established cultural products. The result of this study showed that there was not any historical trace/ story background, which supports the establishment of Rendeng Village original character pottery products. Therefore, it is believed that building a folktale could help the establishment of the original character and overcome the spatial limitation of pottery products marketing. The results of this research expect to be able to provide research results which complement the study around the preservations of cultural products.